Cross-sectional study of the vaginal microbiota in adolescents from the Turkestan Region: a clinical and ecological approach (Bangladesh Journal of Medical Science, 2026)
Background Proper establishment of the vaginal microbiota is critical to adolescent reproductive health. Pubertal hormonal and physiological transitions, compounded by social and environmental stressors, can alter microbiome composition and structure. Given its ecological vulnerabilities, adolescents in Kazakhstan’s Turkistan Region may face a higher risk of vaginal microbiota instability. The objective of this study is to examine the determinants and contributing factors of vaginal discharge in non-sexually active girls aged 13–19 Material and Method This was a cross-sectional study. A total of 211 adolescent girls with no history of sexual activity were included. The cohort was divided into two groups: 98 participants in Group 1 and 113 participants in Group 2. Vaginal and urethral swabs were collected from all subjects, and vaginal discharge samples were analyzed using standard bacteriological techniques. Venous blood was drawn to assess seropositivity. In addition, lead concentrations were measured in hair samples, as well as in water and soil from the participants’ residential environments. Results Vaginal discharge was reported significantly more often in association with dysmenorrhea, lower abdominal pain, malodor, itching, and acne vulgaris (p < 0.05). Bacteriological analysis identified Gardnerella vaginalis, Candida spp., Escherichia coli, and Ureaplasma urealyticum as the predominant pathogens. Elevated lead concentrations were significantly more common in participants with complaints of vaginal discharge. Among environmental biomarkers, hair lead levels demonstrated the highest sensitivity and specificity in predicting the presence of vaginal discharge compared with water and soil measurements. Conclusion: Vaginal discharge in non-sexually active adolescents was linked to both clinical manifestations and environmental lead exposure, highlighting hair lead levels as a valuable diagnostic marker.BJMS, Vol. 25 No. 01 January’26 Page : 327-333